ARTIFICIAL INTELLIGENCE IN ACADEMIC WRITING: CHALLENGES FACED BY ENGLISH LECTURERS IN MAINTAINING ACADEMIC INTEGRITY AND COGNITIVE ENGAGEMENT - Muhammad Taufik Ihsan (State Islamic University of Sultan Syarif Kasim Riau, 2026)
The rapid advancement of artificial intelligence (AI) has significantly transformed the teaching and learning of writing in higher education. Although previous studies have extensively examined students' perceptions of AI-assisted writing tools, relatively limited attention has been devoted to the experiences and challenges encountered by lecturers responsible for teaching writing courses. Therefore, this study investigates the challenges faced by English lecturers in response to the increasing use of AI in students' writing assignments. Employing a qualitative phenomenological approach, the study explores lecturers' experiences related to pedagogical practices, academic integrity, assessment methods, technological adaptation, and administrative responsibilities. Data were collected through semi-structured interviews, classroom observations, and document analysis and were subsequently analyzed using thematic analysis. The findings reveal five major challenges. First, lecturers experience considerable difficulty in distinguishing between students' original work and AI-generated texts. Second, excessive dependence on AI reduces students' engagement in the writing process and limits opportunities for developing critical-thinking skills. Third, conventional assessment methods have become increasingly ineffective, prompting lecturers to adopt more process-oriented approaches. Fourth, lecturers face increasing administrative and professional responsibilities as they continuously adapt their instructional strategies to technological developments. Finally, the study highlights the growing importance of AI literacy among both lecturers and students. The findings suggest that the principal challenge confronting lecturers is not preventing students from using AI but ensuring that these technologies support rather than replace cognitive engagement in the learning process. This study contributes to the growing body of literature on AI-assisted writing by emphasizing the perspectives of lecturers and providing practical recommendations for the ethical and effective integration of AI into higher education.